Mutually exclusive binding of two cellular factors within a critical promoter region of the gene for the IE110k protein of herpes simplex virus. - O'Rourke, D (1993)
We have examined the cis- and trans-acting factors involved in constitutive transcription of the promoter for the IE110k protein of herpes simplex virus type 1. Our results indicate that while the IE110k gene is activated by Vmw65, it also exhibits very efficient constitutive expression approximating that from the simian virus 40 early enhancer-promoter region. We show that despite the presence of multiple copies of the octamer consensus site which mediate Oct-1 binding and subsequent Vmw65 activation, these upstream sequences have a minor effect on constitutive transcription. By progressive exonuclease digestion and subsequent site-directed mutagenesis of the promoter, we have identified a 15-bp region (termed the EC region), from position -89 to -74, which is required for efficient constitutive expression from the IE110k promoter. We demonstrate that two cellular proteins interact with this region and, by competition and methylation interference analyses, show they have distinct but overlapping sequence requirements for binding. One of these proteins is identified as NF-Y, a CCAAT box-binding factor, which binds an inverted CCAAT box located between positions -71 and -75. The second cellular factor, F2, appears to be novel and binds a region with the sequence CGCGCGGC CAT which overlaps the 3' end of the CCAAT box. The terminal AT of the recognition site for F2 represents, on the opposite strand, the terminal AT of the CCAAT box, and these and adjacent bases are critically required for the binding of both factors. These results together with further competition analysis indicate that these factors bind in a mutually exclusive manner to the EC region. The implications of these results for regulation of expression of the IE110k gene are discussed.